Efficacy of nonviral gene transfer of human hepatocyte growth factor - Tsuchihara, Toyokazu; Nukada, Hitoshi; Nakanishi, Kuniaki; Morishita, Ryuichi; Amako, Masatoshi; Arino, Hiroshi; Nemoto, Koichi; Chiba, Kazuhiro; Yagihashi, Soroku (PloS one, 2020)
Ischemic neuropathy is common in subjects with critical limb ischemia, frequently causing chronic neuropathic pain. However, neuropathic pain caused by ischemia is hard to control despite the restoration of an adequate blood flow. Here, we used a rat model of ischemic-reperfusion nerve injury (IRI) to investigate possible effects of hepatocyte growth factor (HGF) against ischemic neuropathy. Hemagglutinating virus of Japan (HVJ) liposomes containing plasmids encoded with HGF was delivered into the peripheral nervous system by retrograde axonal transport following its repeated injections into the tibialis anterior muscle in the right hindlimb. First HGF gene transfer was done immediately after IRI, and repeated at 1, 2 and 3 weeks later. Rats with IRI exhibited pronounced mechanical allodynia and thermal hyperalgesia, decreased blood flow and skin temperature, and lowered thresholds of plantar stimuli in the hind paw. These were all significantly improved by HGF gene transfer, as also were sciatic nerve conduction velocity and muscle action potential amplitudes. Histologically, HGF gene transfer resulted in a significant increase of endoneurial microvessels in sciatic and tibial nerves and promoted nerve regeneration which were confirmed by morphometric analysis. Neovascularization was observed in the contralateral side of peripheral nerves as well. In addition, IRI elevated mRNA levels of P2X3 and P2Y1 receptors, and transient receptor potential vanilloid receptor subtype 1 (TRPV1) in sciatic nerves, dorsal root ganglia and spinal cord, and these elevated levels were inhibited by HGF gene transfer. In conclusion, HGF gene transfer is a potent candidate for treatment of acute ischemic neuropathy caused by reperfusion injury, because of robust angiogenesis and enhanced nerve regeneration.